Combination of Hill Cipher Algorithm and Caesar Cipher Algorithm for Exam Data Security - Agung Agung; Nono Heryana; Arip Solehudin (Buana Information Technology and Computer Sciences (BIT and CS), 2020)
The progress of communication technology has had a positive impact on human life, including in the field of education. The education office is currently implementing computer-based exams starting from the State Higher Education Entrance Joint Selection (SBMPTN) exam to the School Final Examination. But with the implementation of computer-based exams this is of course the less secure the level, therefore the authors make this research with the aim of securing the exam data that will be tested with Hill cipher cryptography and Caesar cipher. Cryptography is a technique of hiding data that is done to secure data, in this case cryptography aims to secure data on exam questions.